2011
DOI: 10.1002/hbm.21378
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cortical degeneration in patients with Parkinson's disease by voxel‐based morphometry, cortical folding, and cortical thickness

Abstract: Noninvasive brain imaging methods provide useful information on cerebral involution and degenerative processes. Here we assessed cortical degeneration in 20 nondemented patients with Parkinson's disease (PD) and 20 healthy controls using three quantitative neuroanatomical approaches: voxel-based morphometry (VBM), cortical folding (BrainVisa), and cortical thickness (FreeSurfer). We examined the relationship between global and regional gray matter (GM) volumes, sulcal indices, and thickness measures derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
154
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 78 publications
14
154
1
2
Order By: Relevance
“…Supporting the present finding, previous studies found no significant difference in volume of white matter of motor cortex (Brenneis et al, 2003;Pereira et al, 2012).…”
Section: White Matter Volume Of Motor Cortexsupporting
confidence: 89%
See 2 more Smart Citations
“…Supporting the present finding, previous studies found no significant difference in volume of white matter of motor cortex (Brenneis et al, 2003;Pereira et al, 2012).…”
Section: White Matter Volume Of Motor Cortexsupporting
confidence: 89%
“…The present finding agrees with studies that found thinning in right precentral area (Pereira et al, 2012;Kim et al, 2014). The present finding disagreed with Koshimori et al (2015), who found significant reduction in cortical thickness in the left precentral gyrus for PD patients instead of the right cortex (Koshimori et al, 2015).…”
Section: Thickness Of Motor Cortexsupporting
confidence: 79%
See 1 more Smart Citation
“…19 In addition, cortical thinning in PD represents a relatively new area of research, and it has been reported to be more sensitive than voxel-based morphometry. 20 Recent studies have shown that cortical thinning occurs in PD without dementia. 21 A longitudinal study also reported that patients with early PD presented with a more aggressive rate of cortical thinning in the frontotemporal regions compared with healthy controls.…”
mentioning
confidence: 99%
“…The results were inconsistent with other studies that have investigated GM using VBM. The inconsistency in the current study might be caused by the increase in the disease duration and the number of subjects included [69][70][71][72].…”
Section: Vbm Analysismentioning
confidence: 85%